2022
DOI: 10.1111/1756-185x.14315
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise training programs with aerobic components on C‐reactive protein, erythrocyte sedimentation rate and self‐assessed disease activity in people with ankylosing spondylitis: A systematic review and meta‐analysis

Abstract: Aim:To examine the effect of exercise training programs with aerobic components on C-reactive protein, erythrocyte sedimentation rate and self-assessed disease activity in people with ankylosing spondylitis compared to non-aerobic rehabilitation.Methods: A systematic review was undertaken of PubMED, Cochrane Library, Embase and Web of Science databases. Articles evaluating the effect of exercise training programs with aerobic components on C-reactive protein, erythrocyte sedimentation rate or Bath Ankylosing S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Further, ASDAS includes the assessment of an inflammation marker. This means that proper exercise performance would affect the course of AS at least in the short‐term, as has been shown in a systematic review 28 . Measurement of BASMI scores includes objective assessment of physical metrics in AS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Further, ASDAS includes the assessment of an inflammation marker. This means that proper exercise performance would affect the course of AS at least in the short‐term, as has been shown in a systematic review 28 . Measurement of BASMI scores includes objective assessment of physical metrics in AS.…”
Section: Discussionmentioning
confidence: 96%
“…This means that proper exercise performance would affect the course of AS at least in the short-term, as has been shown in a systematic review. 28 Measurement of BASMI scores includes objective assessment of physical metrics in AS. Lumbar flexion, cervical rotation, and distance markers (tragus-to-wall and intermalleolar) are components of the BASMI questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The first RCT on UPA in AS patients is the SELECT-AXIS, which showed an early and significant improvement in all the efficacy outcomes, together with a rapid and constant improvement of the patients who switched from placebo. Regarding the safety profile, the most frequent AEs were upper respiratory tract infections, rhinopharyngitis (92,93). Also the addition of a soft-tissue mobilisation to the training programme of AS patients seemed to significantly improve the levels of disease activity and the physical function of patients (94).…”
Section: Jak-inhibitorsmentioning
confidence: 99%
“…• Apremilast did not show significant efficacy in AS (89,90). • An aerobic exercise programme and soft-tissue mobilisation should be added to the individual exercise prescription of AS patients (92)(93)(94). • Home-and-workplace combined exercise could improve the work productivity of AS patients (95).…”
Section: Jak-inhibitorsmentioning
confidence: 99%
“…In Karin's experiment, aerobic exercise was found to significantly improve fitness and reduce peripheral pain in AS patients [34]. Some researchers have also demonstrated that aerobic exercise has a significant effect on promoting the recovery of AS patients [35,36]. Meanwhile, Yoga [37], Pilates [13],…”
Section: Plos Onementioning
confidence: 99%